Functional Diversity of Serotonin Neurons in the Dorsal and Median Raphe Nuclei in Emotional Responses - Yu Ohmura; Kazuki Nagayasu (Neuropsychopharmacology Reports)
ABSTRACT Of serotonergic nuclei in the central nervous system, mainly the dorsal raphe nucleus (DRN) and median raphe nucleus (MRN) project to the forebrain and midbrain; therefore, these nuclei are involved in emotional/cognitive functions and psychiatric disorders. Researchers have often generalized findings from the DRN to represent the functions of the entire serotonergic system, primarily due to the fact that the DRN is the largest serotonergic nucleus and due to the assumption that the serotonergic system operates as a single, cohesive unit. However, recent evidence is challenging this perspective and necessitating a reevaluation. In this brief review, we summarize recent studies demonstrating the functional diversity of the DRN alongside the functional unity of the MRN. These findings suggest that different subpopulations within the serotonergic system may exert opposing effects on emotional functions. Furthermore, this diversity‐aware approach will help settle ongoing debates regarding the serotonin hypothesis of depression, which stems from the difficulty in the application of this approach in humans. We advocate for increased efforts to identify factors associated with these functional subgroups, which could lead to more targeted and effective interventions.